Zero waste home : the ultimate guide to simplifying your life - Johnson, Bea, 1974- (Penguin Random House UK, 2016)
Bea Johnson transformed her family's health, finances, and relationships for the better by reducing their waste to an astonishing half litre per year. It's all down to the 5 Rs: Refuse, Reduce, Reuse, Recycle, Rot (and only in that order!). Zero Waste Home shows how these key principles can be applied to every area of your house from the kitchen to the kids' room, and it's packed with easy tips for all of us: from buying in bulk and clever meal planning to simply refusing unwanted freebies and using your plants as air fresheners. Bea Johnson shows, by inspiring example, what green living looks like and offers a practical, step-by-step guide to diminishing your environmental footprint and improving your life.